SIFAT MEKANIK BETON TANPA AGREGAT KASAR - Daniel Christianto; Tiara Amira Utami; Metta Yoana (JMTS: Jurnal Mitra Teknik Sipil, 2023)
One of the transitional materials in concrete mixes is Reactive Powder Concrete (RPC). There are several mechanical properties that can be used as a reference when judging the quality of concrete. The modulus of elasticity is the ratio of normal stress to associated strain for tensile or compressive stress below the proportional limit of the material. The modification factor (λ) value that reflects the reduction in mechanical properties of lightweight concrete compared to normal weight concrete of the same compressive strength. Until now, references to concrete for mechanical properties are still only intended for normal concrete. In this study tensile, splitting, and elasticity tests would be carried out on RPC without coarse aggregate which refers to the American Society for Testing and Materials (ASTM) standards to analyze the mechanical properties of the concrete with a Universal Testing Machine (UTM) and compressor meter tool which aims to determine the modulus of elasticity and the value of λ of the sample being tested. After testing on cylindrical specimens, the specific gravity ranges from 1884,3945 kg/m3 to 2040,9558 kg/m3, the modulus of elasticity values are 20064,2870 MPa and 34787,6751 MPa, and the λ values range from 1,1944 to 1,8665. Abstrak Salah satu bahan transisi dalam campuran beton adalah Reactive Powder Concrete (RPC). Adapun beberapa sifat mekanik yang dapat dijadikan acuan untuk menentukan kualitas atau mutu beton. Salah satunya adalah modulus elastisitas, yang merupakan rasio tegangan normal terhadap tegangan terkait pada tegangan tarik atau tegangan tekan di bawah batas proporsionalitas material. Faktor modifikasi (λ), yang merefleksikan properti mekanis tereduksi dari beton ringan, semuanya relatif terhadap beton normal dengan kuat tekan yang sama. Acuan ketentuan sifat mekanik beton hingga saat ini hanya ditujukan untuk beton normal. Oleh karena itu, dalam penelitian ini dilakukan pengujian tarik, tekan belah, dan elastisitas pada beton tanpa agregat kasar jenis RPC menurut standar American Society for Testing and Materials (ASTM) untuk menganalisa sifat mekanik dari beton tersebut dengan mesin Universal Testing Mechine (UTM) dan alat kompresor meter yang bertujuan untuk mengetahui modulus elastisitas dan nilai λ dari sampel yang diuji. Setelah dilakukan pengujian pada benda uji silinder, didapatkan berat jenis yang berkisar antara 1884,3945 kg/m3 hingga 2040,9558 kg/m3, nilai modulus elastisitas sebesar 20064,2870 MPa dan 34787,6751, nilai λ yang berkisar antara 1,1944 hingga 1,8665.